Unconventional Fiscal Policy - Francesco D'Acunto; Daniel Hoang; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2018)
Unconventional fiscal policy uses announcements of future increases in consumption taxes to generate inflation expectations and accelerate consumption expenditure. It is budget neutral and time consistent. We provide preliminary evidence for the effectiveness of such policies using changes in value-added tax (VAT) and household survey data for Poland. We find households increased their inflation expectations and willingness to purchase durables before the increase in VAT. Future research has to ensure income, wealth effects, or intratemporal substitution channels cannot explain these results and ideally exploit exogenous variation in VAT in a fixed nominal interest rate environment.
Keywords: D12; D84; D91; E21; E31; E32; E52; E65; 330